Intravascular papillary endothelial hyperplasia along the intrinsic muscle after hand contusion injury: Report of two cases - Chi-Yu Wang; Chung-Chih Hong; Zheng-Yi Huang; Chih-Hsin Wang (Acta Orthopaedica et Traumatologica Turcica, 2019)
Intravascular papillary endothelial hyperplasia (IPEH), also known as Masson's tumor or vegetant intravascular hemangioendothelioma, is a reactive condition representing an exuberant organization and recanalization of a thrombus. It can occur in normal blood vessels or in vascular malformations, perhaps in response to blood vessel injury or thrombosis.In this report, we present the diagnostic and therapeutic courses of a 55 year-old woman and an 18 year-old man, who had a progressive protruding hand mass following a hand contusion. The pathological examination confirmed the diagnosis of IPEH in both patients. Keywords: Hand tumor, Intravascular papillary endothelial hyperplasia, Lumbrical tumor, Vascular tumor, Hand contusion injury